2019
DOI: 10.14202/ijoh.2019.86-91
|View full text |Cite
|
Sign up to set email alerts
|

Potential of medicinal plants to treat dengue

Abstract: Dengue is a major public health challenge worldwide, particularly in tropical areas. Nearly 390 million infections and 22,000 deaths occur every year. At present, there are no specific therapeutics available to treat dengue; however, possible treatment procedures are explained in the traditional medical systems (TMSs), such as Sri Lankan TMS, Indian Ayurvedic, Unani, and Siddha TMS. In these TMSs, medicinal plants have been used in several ways against dengue, such as virocides, larvicides, and mosquito repell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…No drugs are available in the world only suggestive and supportive care is given to the patients (WHO 2023 ). Many drugs have been used which is isolated from natural plants against many types of disease (Kaushik et al 2018 ; Neelawala et al 2019 ). In the current design, the choosen plant ( O. sanctum ) extract was prepared by using a non-conventional method i.e.…”
Section: Discussionmentioning
confidence: 99%
“…No drugs are available in the world only suggestive and supportive care is given to the patients (WHO 2023 ). Many drugs have been used which is isolated from natural plants against many types of disease (Kaushik et al 2018 ; Neelawala et al 2019 ). In the current design, the choosen plant ( O. sanctum ) extract was prepared by using a non-conventional method i.e.…”
Section: Discussionmentioning
confidence: 99%
“…morphine, quinine, quinidine, artemisinine, taxol, aspirin, colchicines, digoxin, tubocurarine, ephedrine, vincristine and vinblastine are available in the market to fight against many types of disease. Anti-dengue virucidal activity of methanol extracts of Andrographis paniculata ; essential oils of Santalum album ; petroleum ether extract of Alternanthera philoxeroides ; ethanol and water extracts of Hippophae rhamnoides; dichloromethane and ethanol extracts of Cladogynos orientalis, Rhizophora apiculata, Flagellaria indica, Houttuynia cordata, and methanolic seed extracts of Quercus lusitanica have already been reported [ 22 , 30 ]. In quantitative term few plants showed anti-dengue activity viz., Kaushik et al study demonstrated that andrographolide extracted from A. paniculata showed 97.23% anti-dengue activity against the dengue-2 virus in C6/36 cell lines [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The triterpenes have a history of medicinal use in many Asian countries. Like oleanolic acid, the other phytochemicals such as quercetin, sulfated galactomannans, 7-O-methyl-glabranine, flavonoids, glabranine, eugenol, ursolic acid, azadirachtin, D-galactose, carrageenan, chalcone 4- hydroxypanduratin A and panduratin isolated from different plants have been reported for anti-dengue virucidal activity [ 22 , 30 ]. Some already reported compounds possess anti-dengue activities are given in Table 3 [ 38 41 ].…”
Section: Discussionmentioning
confidence: 99%